Understanding components of IT risks and enterprise risk management - Ahlan, Abdul Rahman; Arshad, Yusri (InTech - Open Access Publisher, 2011)
This study aims to synthesise the risk factors associated with IT/IS and categorise or classify them into a few main major themes to guide the IT management in their risk management exercises. This chapter is organised into five main sections. First, the chapter begins with introduction to IT and risk in general. Second is the description of methodological approach, review of literature on and description of IT risk, factors and enterprise risk management. Third is the result and discussion of IT risk classification identified from the reviewed articles. Finally, the chapter ends with a brief description of future work.